Leyes y políticas públicas: un estudio internacional comparado sobre Educación Especial en Educación Superior - Hora, Júnio (2023)
The purpose of this essay is to analyze legal proposals and public policies related to the entry and permanence of students with special educational needs in higher education, within a Latin American context that includes Mexico and Brazil. To conduct a comparative study, we use a historical-documentary methodology that examines educational legislation and its impact on public policies between 1996 and 2018. Our theoretical perspective is based on the concept of Civilizing Processes, as developed by Norbert Elias (1993; 1998; 2001; 2006; 2011). This perspective emphasizes how societies utilize social relations between different groups to form their constitution and interdependence processes, which in turn impact the actions of individuals as well as the state institutions that govern them. The data we present in this essay show that Mexico and Brazil have established legal frameworks that recognize the rights of students with special educational needs to access higher education. However, we also question the extent to which these legal documents are effectively implemented and how their failure to materialize can negatively impact our civilizing process, hindering progress towards a society that truly respects diversity and inclusivity.